MEDIATION EFFECT OF KNOWLEDGE SHARING: A CASE STUDY OF MALAYSIAN NGO CULTURE AND EFFECTIVENESS - Mohd Noor, Nurul Hidayana; Abu Bakar Ah, Siti Hajar; Idris, Mohd Awang (Journal of Human Capital Development (JHCD), 2015)
Referring to the resource-based view (RBV), this study aims to examine the mediating effect of knowledge sharing (KS) towards the relationship between organizational culture (OC) and NGO effectiveness (EE). In this study, a total of 190 participants from 19 NGOs in Klang Valley area, Malaysia, were approached with a questionnaire survey. This study only niches its focus on registered welfare and employment NGOs. A total of 144 valid responses were received (75.8 percent of response rate). Regression analysis was used to test the proposed model. The results revealed that KS serves as a partial mediator between OC and EE. The study makes methodological contribution by showing the effect of OC on EE and the role of KS as mediator from the context of Malaysian voluntary sector. Keywords: organizational culture, knowledge sharing, NGO, effectiveness, mediating effect